2018
DOI: 10.3390/su10093175
|View full text |Cite
|
Sign up to set email alerts
|

A Multifaceted Evaluation of Food Waste in a Polish Supermarket—Case Study

Abstract: The objective of this paper is to evaluate the food waste generated in one Polish supermarket in terms of its mass, financial value, and wasted caloric value, and to specify ways in which to manage food that can help contribute to reducing the phenomenon of food waste in commercial facilities. The research material was a list of unsold food items in one supermarket over two weeks. The evaluation shows that in one supermarket, approximately 3.3 tonnes of food was wasted over two weeks, with a total value of €55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…However, it should be emphasized that amounts that are insignificant for the plant itself may be very important for people, who find themselves in a difficult financial situation. The same solution was presented by Bilska et al [34] and based on data demonstrated that two weeks of acceptable losses of milk and milk product in one supermarket could feed 104 women or 82 men aged 31 to 50.…”
Section: Verification Identified Rp On the Basis Of A Surveymentioning
confidence: 87%
“…However, it should be emphasized that amounts that are insignificant for the plant itself may be very important for people, who find themselves in a difficult financial situation. The same solution was presented by Bilska et al [34] and based on data demonstrated that two weeks of acceptable losses of milk and milk product in one supermarket could feed 104 women or 82 men aged 31 to 50.…”
Section: Verification Identified Rp On the Basis Of A Surveymentioning
confidence: 87%
“…The estimated caloric value of dairy products wasted during two weeks amounts to approximately 243.8 kcal. The estimated mass of dairy products appropriated for social purposes would feed from 72 to 174 persons per day (depending on the daily reference value) (Bilska et al, 2018).…”
Section: Challenge Of Reducing Waste Foodmentioning
confidence: 99%
“…Food security and reducing the waste problem, according to different rapports, make up for one of the most important problems of the modern world (EFSA, 2016; RASFF, 2017; FAO, 2017). Its purpose is also to create a sustainable food system which safeguards food and nutrition security in a way (economic, social, and environmental) which does not jeopardise the food and nutrition security of future generations (Bilska et al, 2018; The High Level Panel of Experts, 2014). All people involved in the system of interactions in which one can shape a sustainable consumption have to collaborate actively and interactively in order to teach young people in the spirit of responsible consumption (Popescu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to Garrone et al [13], nearly 60% of surplus food in distribution results from the expiration date. On the basis of the data from 1000 commercial facilities of the hyper format and supermarkets located in Italy, it has been shown that 55% of food with a short shelf life is transferred to organisations dealing with its redistribution to needy people, 35% goes to rendering companies and 10% is used on animal feeding.As shown by Bilska et al [14], retail, despite the fact that it does not have the largest share in the structure of losses, is an important link in the food chain due to the significant amount of food products that can be obtained from this area and be redistributed through public benefit organisations to those in need. The level of food losses generated by all supermarkets operating in 2013 in Poland on an annual basis was estimated at 488,556 tons with a value of €837 million.…”
mentioning
confidence: 99%
“…As shown by Bilska et al [14], retail, despite the fact that it does not have the largest share in the structure of losses, is an important link in the food chain due to the significant amount of food products that can be obtained from this area and be redistributed through public benefit organisations to those in need. The level of food losses generated by all supermarkets operating in 2013 in Poland on an annual basis was estimated at 488,556 tons with a value of €837 million.…”
mentioning
confidence: 99%